SCM-36S molecular sieve, preparation method and application thereof, composition and methanol conversion method

The SCM-36S molecular sieve addresses the limitations of existing sieves by offering thin crystals, large surface area, and high acid content, enhancing catalytic performance in alkylbenzene cracking and methanol conversion.

CN119143150AActive Publication Date: 2024-12-17CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202310716032.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

Existing molecular sieves lack thin crystal thickness, large external specific surface area, and sufficient acid content, which limits their effectiveness in catalytic reactions such as alkylbenzene cracking and methanol conversion to olefins and aromatics.

Method used

The development of SCM-36S molecular sieve with a unique X-ray diffraction pattern, characterized by thin crystal thickness, large external specific surface area, and high strong acid content, achieved through a simple preparation method using a crystallization solution with specific molar ratios of silicon source, sodium aluminate, sodium hydroxide, and an organic structure directing agent containing trimethylethylammonium ions.

Benefits of technology

The SCM-36S molecular sieve exhibits high activity and stability, with fast molecular diffusion, leading to high reactant conversion rates and product yields in alkylbenzene cracking and methanol conversion reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143150A_ABST
    Figure CN119143150A_ABST
Patent Text Reader

Abstract

The invention relates to the field of molecular sieves, in particular to an SCM-36S molecular sieve, a preparation method and application thereof, a composition and a methanol conversion method. The molecular sieve has specific X-ray diffraction pattern characteristics. The SCM-36S molecular sieve with the X-ray diffraction pattern characteristics is thin in crystal thickness, large in external specific surface area, large in acid amount, large in strong acid amount, fast in molecular diffusion and high in activity and stability. The molecular sieve provided by the invention is used for alkyl benzene cracking reaction or methanol conversion to prepare olefin and / or aromatic hydrocarbon, and has the advantages of high reactant conversion rate, high product yield and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of molecular sieves, and in particular to an SCM-36S molecular sieve and a preparation method, application and composition thereof, and a methanol conversion method. Background Art

[0002] In industry, molecular sieve materials are widely used in catalysis, ion exchange, adsorption and separation due to their open structure and large surface area. The subtle differences in the structure of these materials indicate differences in various observable properties used to characterize them, such as their morphology, specific surface area, pore size and the variability of these sizes, and also mean that they themselves have significant differences in the catalytic and adsorption properties of the materials.

[0003] The basic framework structure of crystalline microporous zeolite is based on a rigid three-dimensional TO4 (SiO4, AlO4, etc.) unit structure; in this structure, TO4 shares oxygen atoms in a tetrahedral manner, and the charge balance of the framework tetrahedron such as AlO4 is achieved through surface cations such as Na + , H + The existence of zeolite is maintained. It can be seen that the skeleton properties of zeolite can be changed by cation exchange. At the same time, there is a rich pore system with a certain pore size in the structure of zeolite. These pores are intertwined to form a three-dimensional network structure, and the skeleton can still exist stably after the water or organic matter in the pores is removed (US 4439409). It is based on the above structure that zeolite not only has good catalytic activity and excellent shape selectivity for a variety of organic reactions, but also can achieve good selectivity through modification (US 6162416, US 4954325, US 5362697).

[0004] The specific structure of the molecular sieve is determined by the X-ray diffraction spectrum (XRD), which is measured by an X-ray powder diffractometer using a Cu-Kα ray source and a nickel filter. Different zeolite molecular sieves have different XRD spectrum characteristics. Existing molecular sieves, such as A-type zeolite, Y-type zeolite, MCM-22 molecular sieve, etc., all have their own characteristic XRD spectra.

[0005] At the same time, molecular sieves with the same XRD spectra but different types of framework elements are also different. For example, TS-1 molecular sieve (US 4410501) and ZSM-5 molecular sieve (US 3702886) have the same XRD spectra but different framework elements. Specifically, the framework elements of TS-1 molecular sieve are Si and Ti, which have catalytic oxidation function, while the framework elements of ZSM-5 molecular sieve are Si and Al, which have acid catalysis function.

[0006] In addition, zeolites with the same XRD spectra and the same types of framework elements, but with different relative contents of framework elements, belong to different molecular sieves. For example, X zeolite (US 2882244) and Y zeolite (US 3130007) have the same XRD spectra and both framework elements are Si and Al, but with different relative contents of Si and Al. Specifically, the Si / Al molar ratio of X zeolite is less than 1.5, while the Si / Al molar ratio of Y zeolite is greater than 1.5. Summary of the invention

[0007] The purpose of the present invention is to provide an SCM-36S molecular sieve and its preparation method, application and composition, and methanol conversion method. The SCM-36S molecular sieve has the advantages of thin crystal thickness, large external specific surface area, large acid content, more strong acids, fast molecular diffusion, simple preparation method and high yield, and is a new type of molecular sieve.

[0008] In order to achieve the above object, the present invention provides a SCM-36S molecular sieve in a first aspect. The molecular sieve has an X-ray diffraction pattern as shown in the following table:

[0009]

[0010] Wherein, a: ±0.30°, b: varies with 2θ.

[0011] The second aspect of the present invention provides a method for preparing the molecular sieve described in the present invention, which comprises: preparing a silicon source, sodium aluminate, sodium hydroxide, an organic structure directing agent and water into a crystallization solution, separating and drying after crystallization treatment; wherein the Al2O3 content in the sodium aluminate is 38-43% by weight, and the Na2O content is 30-33% by weight; the organic structure directing agent contains a trimethylethylammonium ion structure; in the crystallization solution, the molar ratio of the silicon source in terms of SiO2, the sodium aluminate in terms of Al2O3, the sodium hydroxide, the organic structure directing agent in terms of trimethylethylammonium ions and water is 1:0.016-0.050:0.10-0.20:0.15-0.30:10-50.

[0012] The third aspect of the present invention provides a use of the molecular sieve of the present invention in the preparation of an adsorbent and / or a catalyst.

[0013] A fourth aspect of the present invention provides a composition comprising the molecular sieve described in the present invention.

[0014] A fifth aspect of the present invention provides an application of the molecular sieve of the present invention in alkylbenzene cracking reaction or methanol conversion to olefins and / or aromatics.

[0015] A sixth aspect of the present invention provides a methanol conversion method, which comprises: contacting methanol with a catalyst to react to obtain olefins and / or aromatics, wherein the catalyst comprises the molecular sieve described in the present invention.

[0016] Through the above technical solution, the present invention has the following advantages:

[0017] The SCM-36S molecular sieve having the X-ray diffraction pattern characteristics of the present invention has thin crystal thickness, large external specific surface area, large acid content, high strong acid content, fast molecular diffusion, and high activity and stability.

[0018] The molecular sieve of the present invention is prepared by the method of the present invention, and the preparation method is simple and has a high yield.

[0019] The molecular sieve of the present invention is used for alkylbenzene cracking reaction or methanol conversion to produce olefins and / or aromatics, and has high reactant conversion rate and product yield and long service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the X-ray diffraction pattern (XRD) of the sample in Example 1;

[0021] Figure 2 is a scanning electron microscope image (SEM) of the sample in Example 1;

[0022] Figure 3 is a transmission electron microscope (TEM) image of the sample in Example 1;

[0023] Figure 4 is the X-ray diffraction pattern (XRD) of the sample in Example 2;

[0024] Figure 5 is a scanning electron microscope image (SEM) of the sample in Example 2;

[0025] Figure 6 is the X-ray diffraction pattern (XRD) of the sample in Example 3;

[0026] Figure 7 is a scanning electron microscope image (SEM) of the sample in Example 3;

[0027] Figure 8 is the X-ray diffraction pattern (XRD) of the sample in Example 4;

[0028] Fig. 9 is the X-ray diffraction pattern (XRD) of the sample in Comparative Example 1;

[0029] Fig.10 This is the X-ray diffraction pattern (XRD) of the sample in Comparative Example 2. DETAILED DESCRIPTION

[0030] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0031] The present invention provides a SCM-36S molecular sieve having an X-ray diffraction pattern as shown in the following table:

[0032]

[0033] Wherein, a: ±0.30°, b: varies with 2θ.

[0034] The SCM-36S molecular sieve provided by the present invention has the above-mentioned characteristics, so that the molecular sieve has a unique crystal structure, thin crystal thickness, large external specific surface area, large acid content, more strong acids, fast molecular diffusion, and high activity.

[0035] According to a preferred embodiment of the present invention, the molecular sieve has a schematic chemical composition of "SiO2·1 / nAl2O3·1 / mR", 20≤n≤60, 0.04≤m≤0.15; preferably 25≤n≤50, 0.05≤m≤0.14; wherein R is an organic structure directing agent.

[0036] According to a preferred embodiment of the present invention, the molecular sieve crystals have a flake morphology with a thickness of no more than 12 nm, a length and a width of 100-550 nm respectively; preferably, the molecular sieve crystals have a flake morphology with a thickness of no more than 10 nm, a length and a width of 120-450 nm respectively.

[0037] According to a preferred embodiment of the present invention, the crystals with a thickness of no more than 6 nm in the molecular sieve account for at least 60% of the total crystals.

[0038] According to a preferred embodiment of the present invention, the molecular sieve is a sodium type molecular sieve: the total specific surface area is not less than 350 m 2 / g, preferably 350-600 m 2 / gram.

[0039] According to a preferred embodiment of the present invention, the molecular sieve is a sodium type molecular sieve: the external specific surface area is not less than 180 m 2 / g, preferably 180-300 m 2 / gram.

[0040] According to a preferred embodiment of the present invention, the molecular sieve is a sodium type molecular sieve: the total pore volume is not less than 1.30 cm 3 / g, preferably 1.30-2.0 cm 3 / gram.

[0041] According to a preferred embodiment of the present invention, the molecular sieve is a sodium type molecular sieve: the micropore volume is not less than 0.08 cm 3 / g, preferably 0.08-0.20 cm 3 / gram.

[0042] According to a preferred embodiment of the present invention, the molecular sieve is a sodium type molecular sieve: the pore diameter is 0.30-0.70 nanometers, preferably 0.35-0.65 nanometers.

[0043] In the present invention, the sodium type molecular sieve is obtained by subjecting the dried molecular sieve to a first calcination treatment.

[0044] In the present invention, the sodium type molecular sieve is converted into the hydrogen type molecular sieve through ammonium exchange and second calcination.

[0045] According to a preferred embodiment of the present invention, the molecular sieve is a hydrogen-type molecular sieve: the total acid content is not less than 600 μmol / g, preferably 600-1600 μmol / g.

[0046] According to a preferred embodiment of the present invention, the molecular sieve is a hydrogen-type molecular sieve: the amount of strong acid is not less than 200 μmol / g, preferably 200-600 μmol / g.

[0047] In the present invention, there is no special requirement for the preparation method of the molecular sieve, as long as a molecular sieve with the aforementioned characteristics can be obtained. According to a preferred embodiment of the present invention, the present invention provides a preparation method of the molecular sieve of the present invention, the method comprising: preparing a silicon source, sodium aluminate, sodium hydroxide, an organic structure directing agent and water into a crystallization solution, separating and drying after crystallization treatment; wherein the content of Al2O3 in the sodium aluminate is 38-43% by weight, and the content of Na2O is 30-33% by weight; the organic structure directing agent contains a trimethylethylammonium ion structure; in the crystallization solution, the molar ratio of the silicon source in terms of SiO2, the sodium aluminate in terms of Al2O3, the sodium hydroxide, the organic structure directing agent in terms of trimethylethylammonium ions and water is 1: 0.016-0.050: 0.10-0.20: 0.15-0.30: 10-50.

[0048] By adopting the method of the present invention, a molecular sieve having the aforementioned characteristics of the present invention can be directly synthesized with a high synthesis yield by using a cheap and simple organic structure directing agent containing a trimethylethylammonium ion structure. The synthesized SCM-36S molecular sieve has a large external specific surface area, a large acid content, and a large amount of strong acid.

[0049] In the present invention, the optional range of the silicon source is relatively wide. According to a preferred embodiment of the present invention, the silicon source is selected from at least one of silica sol, silica gel and white carbon black.

[0050] In the present invention, all organic structure directing agents having a trimethylethylammonium ion structure are suitable for the present invention. According to a preferred embodiment of the present invention, the organic structure directing agent is a quaternary ammonium salt and / or a quaternary ammonium base containing a trimethylethylammonium ion structure, preferably selected from at least one of trimethylethylammonium hydroxide, trimethylethylammonium chloride, trimethylethylammonium bromide and trimethylethylammonium iodide, and more preferably trimethylethylammonium hydroxide.

[0051] According to a preferred embodiment of the present invention, in the crystallization solution, the molar ratio of the silicon source as SiO2, the sodium aluminate as Al2O3, the sodium hydroxide, the organic structure directing agent as trimethylethylammonium ion and water is 1: 0.019-0.045: 0.12-0.18: 0.16-0.30: 12-45.

[0052] In the present invention, the conditions for the crystallization treatment may be conventionally selected in the art. According to a preferred embodiment of the present invention, the conditions for the crystallization treatment include: a temperature of 150-180°C, preferably 155-175°C.

[0053] The conditions of the crystallization treatment include: a time of 1.5-9.0 days and a crystallization time of 2.0-8.0 days.

[0054] In the present invention, there is no special requirement for the crystallization method. According to a preferred embodiment of the present invention, the crystallization method is dynamic crystallization with rotation and / or stirring, with a rotation speed of 10-60 rpm, and / or a stirring speed of 30-300 rpm.

[0055] In the present invention, the drying conditions may be conventionally selected in the art. According to a preferred embodiment of the present invention, the drying conditions include: a temperature of 40-250°C, preferably 60-50°C.

[0056] According to a preferred embodiment of the present invention, the drying conditions include: a time of 8-30 hours, preferably 10-20 hours.

[0057] According to a preferred embodiment of the present invention, the method further comprises: performing a first calcination treatment after drying.

[0058] In the present invention, the conditions for the first calcination can be conventionally selected in the art. According to a preferred embodiment of the present invention, the conditions for the first calcination include: a calcination temperature of 300-800°C, preferably 400-650°C.

[0059] According to a preferred embodiment of the present invention, the conditions for the first calcination include: a time of 1-10 hours, preferably 3-6 hours.

[0060] According to a preferred embodiment of the present invention, the method further comprises: performing ammonium exchange after the first calcination treatment.

[0061] In the present invention, the conditions for ammonium exchange may be conventionally selected in the art. According to a preferred embodiment of the present invention, the conditions for ammonium exchange include: the ammonium salt is selected from at least one of ammonium chloride, ammonium nitrate, ammonium carbonate and ammonium sulfate.

[0062] According to a preferred embodiment of the present invention, the conditions for the ammonium exchange include: the concentration of ammonium ions in the ammonium salt solution is 0.1-1 mol / L.

[0063] According to a preferred embodiment of the present invention, the conditions for the ammonium exchange include: a solid-liquid ratio of 1:5-1:20.

[0064] According to a preferred embodiment of the present invention, the conditions for the ammonium exchange include: a temperature of 30-80°C.

[0065] According to a preferred embodiment of the present invention, the conditions for the ammonium exchange include: a time of 1-8 hours.

[0066] According to a preferred embodiment of the present invention, the method further comprises: performing a second calcination after the ammonium exchange.

[0067] In the present invention, the conditions for the second calcination can be conventionally selected in the art. According to a preferred embodiment of the present invention, the conditions for the second calcination include: a calcination temperature of 300-800°C, preferably 400-700°C.

[0068] According to a preferred embodiment of the present invention, the time is 1-8 hours, preferably 2-6 hours.

[0069] The present invention provides an application of the molecular sieve in the preparation of an adsorbent and / or a catalyst.

[0070] The present invention provides a composition, which comprises the molecular sieve of the present invention.

[0071] The present invention provides an application of the molecular sieve of the present invention in alkylbenzene cracking reaction or methanol conversion to produce olefins and / or aromatics.

[0072] The present invention provides a methanol conversion method, which comprises: contacting methanol with a catalyst to react to obtain olefins and / or aromatics, wherein the catalyst comprises the molecular sieve described in the present invention.

[0073] The molecular sieve of the present invention is used for converting methanol to prepare olefins and / or aromatics, and has the characteristics of high activity and long life.

[0074] According to the present invention, the molecular sieve obtained above can be used in any physical form, such as powder, granule or molded product (such as strip, clover, etc.). These physical forms can be obtained in any conventional manner known in the art without particular limitation.

[0075] In the context of this specification, in the XRD data of molecular sieves, w, m, s, vs represent the diffraction peak intensity, w is weak, m is medium, s is strong, vs is very strong, which is well known to those skilled in the art. Generally speaking, w is less than 20; m is 20-40; s is 40-70; vs is greater than 70.

[0076] In the context of this specification, the structure of the molecular sieve is determined by an X-ray diffraction spectrum (XRD), which is measured by an X-ray powder diffractometer using a Cu-Kα ray source and a nickel filter. Before the sample test, a scanning electron microscope (SEM) is used to observe the crystallization of the molecular sieve sample to confirm that the sample contains only one type of crystal, that is, the molecular sieve sample is a pure phase, and on this basis, an XRD test is performed to ensure that there are no interference peaks of other crystals in the diffraction peaks in the XRD spectrum.

[0077] In the context of this specification, including the following examples and comparative examples, the molecular sieve X-ray powder diffractometer model is Panalytical X PERPRO X-ray powder diffractometer, the phase of the sample is analyzed, and the CuKα ray source is Nickel filter, 2θ scanning range 2~50°, operating voltage 40KV, current 40mA, scanning rate 10° / min.

[0078] In the context of this specification, including in the following examples and comparative examples, the model of the molecular sieve scanning electron microscope (SEM) is S-4800II field emission scanning electron microscope. The molecular sieve is observed at a magnification of 40,000 times using the scanning electron microscope, and an observation field is randomly selected to calculate the average value of the sum of the particle sizes of all crystals in the observation field, and the operation is repeated 10 times in total. The average value of the sum of the 10 average values ​​is taken as the crystal particle size.

[0079] In the context of this specification, including in the following embodiments and comparative examples, the method for measuring the crystal thickness of the molecular sieve is: use a transmission electron microscope (G2F30 transmission electron microscope of FEI Company of the Netherlands, working voltage 300kV) to observe the molecular sieve at a magnification of 100,000 times, randomly select an observation field, and calculate the average value of the sum of the thickness of all the lamellar crystals in the observation field. Repeat this operation for a total of 10 times. The average value of the sum of the average values ​​of 10 times is used as the crystal thickness. Measure the thickness of all crystals in the observation field, and the number of crystals with a thickness not higher than 8nm accounts for the proportion of the total number of crystals, and repeat this operation 5 times. The average value of 5 times is used as the proportion of the number of crystals not higher than 8nm.

[0080] In the context of this specification, including in the following examples and comparative examples, the micropore diameter, pore volume, specific surface area, and external specific surface area of ​​the molecular sieve are measured by nitrogen physical adsorption and desorption method (BET method): the nitrogen physical adsorption and desorption isotherm of the molecular sieve is measured by a physical adsorption instrument (Micromeretic ASAP2020M physical adsorption instrument), and then calculated by the BET equation and t-plot equation. The experimental conditions for the molecular sieve are: the measurement temperature is -196°C, and the molecular sieve is heat-treated at 550°C in an air atmosphere for 6 hours before measurement, and then pre-treated at 350°C in vacuum for 4 hours.

[0081] In the context of this specification, including in the following examples and comparative examples, the molecular sieve inductively coupled plasma atomic emission spectrometer (ICP) model is Varian 725-ES, and the analysis sample is dissolved with hydrofluoric acid to detect the content of the element in moles.

[0082] In the context of this specification, including the following examples and comparative examples, the acidity of the molecular sieve is determined by using the NH3-TPD chemical adsorption-desorption curve using the Altamira AMI-3300 instrument. Before the test, the sample is activated at 550°C for 1 hour, ammonia is adsorbed at 100°C for 20 minutes, and then desorption is detected at 100-600°C. Through Gaussian distribution peak separation, the acidity corresponding to the desorption temperature above 300°C can be considered as the acidity of a strong acid.

[0083] In the context of this specification, including in the following examples and comparative examples, the yield of molecular sieve refers to the percentage of the mass of the sample after calcination to the sum of the mass of SiO2 and Al2O3 contained in the raw materials.

[0084] In the context of this specification, including in the following examples and comparative examples, the catalyst is applied to a methanol conversion reaction:

[0085] The methanol conversion reaction uses methanol as a raw material and converts it into hydrocarbons such as olefins and aromatics under the action of a catalyst.

[0086] Conversion rate of methanol % = (molar amount of feed methanol - molar amount of methanol in the product - 2 × molar amount of dimethyl ether in the product) / (molar amount of feed methanol) × 100%;

[0087] The selectivity of C2-C4 olefin (%) = (2×the molar amount of C2 olefin in the product + 3×the molar amount of C3 olefin in the product + 4×the molar amount of C4 olefin in the product) / (the molar amount of feed methanol - the molar amount of methanol in the product - 2×the molar amount of dimethyl ether in the product) × 100%.

[0088] Selectivity of aromatics (%) = (6×molar amount of benzene in the product + 7×molar amount of toluene in the product + 8×molar amount of xylene in the product) / (molar amount of feed methanol - molar amount of methanol in the product - 2×molar amount of dimethyl ether in the product) × 100%.

[0089] The present invention will be described in detail below through examples.

[0090] Example 1

[0091] 14.35 g of deionized water, 0.604 g of sodium aluminate (containing 40.5% by weight of Al2O3, 30.6% by weight of Na2O, and the balance being H2O), 0.366 g of sodium hydroxide, 7.06 g of trimethylethylammonium hydroxide solution (containing 25.00% by weight of trimethylethylammonium hydroxide) (organic structure directing agent R) and 12.60 g of silica sol (containing 40.0% by weight of SiO2) were stirred at room temperature for 4 hours to obtain a mixture. The final material ratio (molar ratio) was:

[0092] SiO2 / Al2O3=35;

[0093] NaOH / SiO2=0.18;

[0094] Trimethylethylammonium hydroxide (R) / SiO2 = 0.20;

[0095] H2O / SiO2=18.

[0096] The mixture was placed in a stainless steel reactor and heated for crystallization at 170°C and 20 rpm for 3 days. After crystallization, the product was filtered, washed, and dried in an oven at 100°C overnight. The XRD spectrum of the obtained product is shown in the figure below. Figure 1 As shown in Table 1, it is SCM-36S molecular sieve. The SiO2 / Al2O3 molar ratio of the molecular sieve measured by inductively coupled plasma atomic emission spectroscopy (ICP) is 35.1, and the chemical composition of the sample is "1SiO2·0.028Al2O3·0.08R". The SEM electron microscope image of the sample is as follows Figure 2 As shown in the TEM electron microscope image Figure 3 As shown, the crystals have a nano-sheet morphology, with a length of 300 nm, a width of 240 nm, a crystal thickness of 9 nm, and sheet crystals with a thickness not higher than 6 nm account for 65% of the total number of crystals counted.

[0097] Table 1

[0098]

[0099] The molecular sieve yield was 87 wt% after calcination in air at 550°C for 6 hours. The specific surface area of ​​the molecular sieve was 442 m 2 / g, the external specific surface area measured by BET method is 226 m 2 / g; total pore volume 1.69 cm 3 / g, micropore volume is 0.11 cm 3 / gram, the micropore diameter is 0.56nm. The sodium type SCM-36S molecular sieve was exchanged with 0.2mol / L NH4NO3 solution (mass ratio 1:20) at 65°C for ammonium ions for 2 hours, then centrifuged and washed. The sample obtained after repeating the ammonium ion exchange twice was dried at 100°C overnight, and calcined in air at 550°C for 4 hours to obtain the hydrogen type SCM-36S molecular sieve sample. The total acid content of the molecular sieve was 1180μmol / g and the strong acid content was 441μmol / g as measured by NH3-TPD.

[0100] Example 2

[0101] 12.82 g of deionized water, 0.650 g of sodium aluminate (containing 40.5% by weight of Al2O3, 30.6% by weight of Na2O, and the balance being H2O), 0.177 g of sodium hydroxide, 5.47 g of trimethylethylammonium hydroxide solution (containing 25.00% by weight of trimethylethylammonium hydroxide) (organic structure directing agent R) and 10.86 g of silica sol (containing 40.0% by weight of SiO2) were stirred at room temperature for 4 hours to obtain a mixture. The final material ratio (molar ratio) was:

[0102] SiO2 / Al2O3=28;

[0103] NaOH / SiO2=0.15;

[0104] Trimethylethylammonium hydroxide (R) / SiO2=0.18;

[0105] H2O / SiO2=18.

[0106] The mixture was placed in a stainless steel reactor and heated for crystallization at 165°C and 20 rpm for 4 days. After crystallization, the product was filtered, washed, and dried in an oven at 100°C overnight. The XRD spectrum of the obtained product is shown in the figure below. Figure 4As shown in Table 2, it is SCM-36S molecular sieve. The SiO2 / Al2O3 molar ratio of the molecular sieve measured by inductively coupled plasma atomic emission spectroscopy (ICP) is 27.7, and the chemical composition of the sample is "1SiO2·0.036Al2O3·0.07R". The SEM electron microscope image of the sample is as follows Figure 5 As shown, TEM electron microscope image and Figure 3 Similarly, the crystals have a nano-sheet morphology, with a length of 320 nm, a width of 260 nm, a crystal thickness of 9 nm, and sheet-like crystals with a thickness of no more than 7 nm account for 65% of the total number of crystals counted.

[0107] Table 2

[0108]

[0109] The molecular sieve yield was 88 wt% after calcination in air at 550 °C for 6 hours. The specific surface area of ​​the molecular sieve was 489 m 2 / g, the external specific surface area measured by BET method is 245 m 2 / g; total pore volume 1.96 cm 3 / g, micropore volume is 0.11 cm 3 / gram, the micropore diameter is 0.56nm. The sodium type SCM-36S molecular sieve was exchanged with 0.2mol / L NH4NO3 solution (mass ratio 1:20) at 65°C for ammonium ions for 2 hours, then centrifuged and washed. The sample obtained after repeating the ammonium ion exchange twice was dried at 100°C overnight, and calcined in air at 550°C for 4 hours to obtain the hydrogen type SCM-36S molecular sieve sample. The total acid content of the molecular sieve was 1346μmol / g and the strong acid content was 488μmol / g as measured by NH3-TPD.

[0110] Example 3

[0111] 4.77 g of deionized water, 0.481 g of sodium aluminate (containing 40.5% by weight of Al2O3, 30.6% by weight of Na2O, and the balance being H2O), 0.085 g of sodium hydroxide, 6.03 g of trimethylethylammonium hydroxide solution (containing 25.00% by weight of trimethylethylammonium hydroxide) (organic structure directing agent R) and 8.61 g of silica sol (containing 40.0% by weight of SiO2) were stirred at room temperature for 4 hours to obtain a mixture. The final material ratio (molar ratio) was:

[0112] SiO2 / Al2O3=30;

[0113] NaOH / SiO2=0.12;

[0114] Trimethylethylammonium hydroxide (R) / SiO2 = 0.25;

[0115] H2O / SiO2=14.

[0116] The mixture was placed in a stainless steel reactor and heated for crystallization at 160°C and 30 rpm for 6 days. After crystallization, the product was filtered, washed, and dried in an oven at 100°C overnight. The XRD spectrum of the obtained product is shown in the figure below. Figure 6 As shown in Table 3, it is SCM-36S molecular sieve. The SiO2 / Al2O3 molar ratio of the molecular sieve measured by inductively coupled plasma atomic emission spectroscopy (ICP) is 29.8, and the chemical composition of the sample is "1SiO2·0.033Al2O3·0.11R". The SEM electron microscope image of the sample is as follows Figure 7 As shown, TEM electron microscope image and Figure 3 Similarly, the crystals have a nano-sheet morphology, with a length of 280 nm, a width of 240 nm, a crystal thickness of 10 nm, and sheet-like crystals with a thickness of no more than 7 nm account for 65% of the total number of crystals counted.

[0117] Table 3

[0118]

[0119] The molecular sieve yield was 90 wt% after calcination in air at 550°C for 6 hours. The specific surface area of ​​the molecular sieve was 505 m 2 / g, the external specific surface area measured by BET method is 249 m 2 / g; total pore volume 1.71 cm 3 / g, micropore volume is 0.10 cm 3 / gram, the micropore diameter is 0.57nm. The sodium type SCM-36S molecular sieve was exchanged with 0.2mol / L NH4NO3 solution (mass ratio 1:20) at 65°C for ammonium ions for 2 hours, then centrifuged and washed. The sample obtained after repeating the ammonium ion exchange twice was dried at 100°C overnight, and calcined in air at 550°C for 4 hours to obtain the hydrogen type SCM-36S molecular sieve sample. The total acid content of the molecular sieve was 1206μmol / g and the strong acid content was 461μmol / g as measured by NH3-TPD.

[0120] Example 4

[0121] The raw materials and preparation steps are the same as in Example 1, and the raw material ratio is adjusted. The final material ratio (molar ratio) is:

[0122] SiO2 / Al2O3=40;

[0123] NaOH / SiO2=0.16;

[0124] Trimethylethylammonium hydroxide (R) / SiO2 = 0.30;

[0125] H2O / SiO2=22.

[0126] The mixture was placed in a stainless steel reactor and heated for crystallization at 155°C and 10 rpm for 7 days. After crystallization, the product was filtered, washed, and dried in an oven at 100°C overnight. The XRD spectrum of the obtained product is shown in the figure below. Figure 8 As shown in Table 4, it is SCM-36S molecular sieve. The SiO2 / Al2O3 molar ratio of the molecular sieve measured by inductively coupled plasma atomic emission spectroscopy (ICP) is 40.3, and the molar chemical composition of the sample is "1SiO2·0.025Al2O3·0.14R". Figure 2 Similarly, TEM electron microscope images and Figure 3 Similarly, the crystals have a nano-sheet morphology, with a length of 310 nm, a width of 230 nm, a crystal thickness of 11 nm, and sheet crystals with a thickness of no more than 8 nm account for 70% of the total number of crystals counted.

[0127] Table 4

[0128]

[0129]

[0130] The molecular sieve yield was 85 wt% after calcination in air at 550 °C for 6 hours. The specific surface area of ​​the molecular sieve was 428 m 2 / g, the external specific surface area measured by BET method is 220 m 2 / g; total pore volume 1.72 cm 3 / g, micropore volume is 0.11 cm 3 / gram, the micropore diameter is 0.55nm. The sodium type SCM-36S molecular sieve was exchanged with 0.2mol / L NH4NO3 solution (mass ratio 1:20) at 65℃ for 2 hours, then centrifuged and washed. The sample obtained after repeating the ammonium ion exchange twice was dried at 100℃ overnight, and calcined in air at 550℃ for 4 hours to obtain the hydrogen type SCM-36S molecular sieve sample. The total acid content of the molecular sieve was 985μmol / g and the strong acid content was 389μmol / g as measured by NH3-TPD.

[0131] Example 5

[0132] The raw materials and preparation steps are the same as in Example 1, and the raw material ratio is adjusted. The final material ratio (molar ratio) is:

[0133] SiO2 / Al2O3=45;

[0134] NaOH / SiO2=0.14;

[0135] Trimethylethylammonium hydroxide (R) / SiO2=0.24;

[0136] H2O / SiO2=25.

[0137] The mixture was placed in a stainless steel reactor and heated for crystallization at 175°C and 20 rpm for 2.5 days. After crystallization, the product was filtered, washed, and dried in an oven at 100°C overnight. Figure 1 Similarly, as shown in Table 5, it is SCM-36S molecular sieve. The SiO2 / Al2O3 molar ratio of the molecular sieve measured by inductively coupled plasma atomic emission spectroscopy (ICP) is 44.4, and the chemical composition of the sample is "1SiO2·0.022Al2O3·0.10R". The SEM electron microscope image of the sample is Figure 2 Similarly, TEM electron microscope images and Figure 3 Similarly, the crystals have a nano-sheet morphology, with a length of 320 nm, a width of 270 nm, a crystal thickness of 12 nm, and sheet-like crystals with a thickness of no more than 8 nm account for 65% of the total number of crystals counted.

[0138] Table 5

[0139]

[0140] The molecular sieve yield was 91 wt% after calcination in air at 550°C for 6 hours. The specific surface area of ​​the molecular sieve was 452 m 2 / g, the external specific surface area measured by BET method is 246 m 2 / g; total pore volume 1.86 cm 3 / g, micropore volume is 0.10 cm 3 / gram, the micropore diameter is 0.58nm. The sodium type SCM-36S molecular sieve was exchanged with 0.2mol / L NH4NO3 solution (mass ratio 1:20) at 65℃ for 2 hours, then centrifuged and washed. The sample obtained after repeating the ammonium ion exchange twice was dried at 100℃ overnight, and calcined in air at 550℃ for 4 hours to obtain the hydrogen type SCM-36S molecular sieve sample. The total acid content of the molecular sieve was 867μmol / g and the strong acid content was 372μmol / g as measured by NH3-TPD.

[0141] Example 6

[0142] The raw materials and preparation steps are the same as those in Example 1, the organic structure directing agent is trimethylethylammonium bromide (R), and the raw material ratio is adjusted, and the final material ratio (molar ratio) is:

[0143] SiO2 / Al2O3=50;

[0144] NaOH / SiO2=0.12;

[0145] Trimethylethylammonium bromide (R) / SiO2=0.28;

[0146] H2O / SiO2=28.

[0147] The mixture was placed in a stainless steel reactor and heated for crystallization at 170°C and 40 rpm for 3.5 days. After crystallization, the product was filtered, washed, and dried in an oven at 100°C overnight. Figure 1 Similarly, as shown in Table 6, it is SCM-36S molecular sieve. The SiO2 / Al2O3 molar ratio of the molecular sieve measured by inductively coupled plasma atomic emission spectroscopy (ICP) is 49.4, and the chemical composition of the sample is "1SiO2·0.020Al2O3·0.10R". The SEM electron microscope image of the sample is Figure 2 Similarly, TEM electron microscope images and Figure 3 Similarly, the crystals have a nano-sheet morphology, with a length of 300 nm, a width of 230 nm, a crystal thickness of 10 nm, and sheet crystals with a thickness of no more than 7 nm account for 65% of the total number of crystals counted.

[0148] Table 6

[0149]

[0150] The molecular sieve yield was 88 wt% after calcination in air at 550 °C for 6 hours. The specific surface area of ​​the molecular sieve was 467 m 2 / g, the external specific surface area measured by BET method is 214 m 2 / g; total pore volume 1.79 cm 3 / g, micropore volume is 0.12 cm 3 / gram, the micropore diameter is 0.56nm. The sodium type SCM-36S molecular sieve was exchanged with 0.2mol / L NH4NO3 solution (mass ratio 1:20) at 65°C for ammonium ions for 2 hours, then centrifuged and washed. The sample obtained after repeating the ammonium ion exchange twice was dried at 100°C overnight, and calcined in air at 550°C for 4 hours to obtain the hydrogen type SCM-36S molecular sieve sample. The total acid content of the molecular sieve was 775μmol / g and the strong acid content was 276μmol / g as measured by NH3-TPD.

[0151] Example 7

[0152] The raw materials and preparation steps are the same as those in Example 1, the organic structure directing agent is trimethylethylammonium chloride (R), and the raw material ratio is adjusted, and the final material ratio (molar ratio) is:

[0153] SiO2 / Al2O3=25;

[0154] NaOH / SiO2=0.16;

[0155] Trimethylethylammonium chloride (R) / SiO2 = 0.22;

[0156] H2O / SiO2=36.

[0157] The mixture was placed in a stainless steel reactor and heated for crystallization at 165°C and 20 rpm for 5 days. After crystallization, the product was filtered, washed, and dried in an oven at 100°C overnight. Figure 1 Similarly, as shown in Table 7, it is SCM-36S molecular sieve. The SiO2 / Al2O3 molar ratio of the molecular sieve measured by inductively coupled plasma atomic emission spectroscopy (ICP) is 24.7, and the chemical composition of the sample is "1SiO2·0.040Al2O3·0.07R". The SEM electron microscope image of the sample is Figure 2 Similarly, TEM electron microscope images and Figure 3 Similarly, the crystals have a nano-sheet morphology, with a length of 290 nm, a width of 190 nm, a crystal thickness of 10 nm, and sheet-like crystals with a thickness of no more than 6 nm account for 65% of the total number of crystals counted.

[0158] Table 7

[0159]

[0160] The molecular sieve yield was 85 wt% after calcination in air at 550°C for 6 hours. The specific surface area of ​​the molecular sieve was 422 m 2 / g, the external specific surface area measured by BET method is 209 m 2 / g; total pore volume 1.58 cm 3 / g, micropore volume is 0.11 cm 3 / gram, the micropore diameter is 0.56nm. The sodium type SCM-36S molecular sieve was exchanged with 0.2mol / L NH4NO3 solution (mass ratio 1:20) at 65°C for ammonium ions for 2 hours, then centrifuged and washed. The sample obtained after repeating the ammonium ion exchange twice was dried at 100°C overnight, and calcined in air at 550°C for 4 hours to obtain the hydrogen type SCM-36S molecular sieve sample. The total acid content of the molecular sieve was 1486μmol / g, and the strong acid content was 524μmol / g as measured by NH3-TPD.

[0161] Example 8

[0162] The raw materials and preparation steps are the same as in Example 1, and the raw material ratio is adjusted. The final material ratio (molar ratio) is:

[0163] SiO2 / Al2O3=21;

[0164] NaOH / SiO2=0.18;

[0165] Trimethylethylammonium hydroxide (R) / SiO2 = 0.20;

[0166] H2O / SiO2=18.

[0167] The mixture was placed in a stainless steel reactor and heated for crystallization at 170°C and 20 rpm for 3 days. After crystallization, the product was filtered, washed, and dried in an oven at 100°C overnight. Figure 1 Similar to Table 1, it is SCM-36S molecular sieve. The SiO2 / Al2O3 molar ratio of the molecular sieve measured by inductively coupled plasma atomic emission spectroscopy (ICP) is 20.8, and the molar chemical composition of the sample is "1SiO2·0.048Al2O3·0.07R". Figure 2 Similarly, the crystals have a nano-sheet morphology, with a length of 530 nm, a width of 420 nm, a crystal thickness of 12 nm, and sheet-like crystals with a thickness of no more than 6 nm account for 60% of the total number of crystals counted.

[0168] The molecular sieve yield was 81 wt% after calcination in air at 550°C for 6 hours. The specific surface area of ​​the molecular sieve was 409 m 2 / g, the external specific surface area measured by BET method is 184 m 2 / g; total pore volume 0.92 cm 3 / g, micropore volume is 0.10 cm 3 / gram, the micropore diameter is 0.56nm. The sodium type SCM-36S molecular sieve was exchanged with 0.2mol / L NH4NO3 solution (mass ratio 1:20) at 65°C for ammonium ions for 2 hours, then centrifuged and washed. The sample obtained after repeating the ammonium ion exchange twice was dried at 100°C overnight, and calcined in air at 550°C for 4 hours to obtain the hydrogen type SCM-36S molecular sieve sample. The total acid content of the molecular sieve was 1561μmol / g, and the strong acid content was 542μmol / g as measured by NH3-TPD.

[0169] Embodiments 9 to 16

[0170] Take the H-type SCM-36S molecular sieve powder samples of Examples 1 to 8 (corresponding to Examples 9 to 16, respectively, for example, the molecular sieve of Example 1 corresponds to the specific implementation of Example 9), crush and sieve out 1.0 g of the 20-40 mesh particle size portion and put it into a fixed bed reactor for methanol conversion reaction. The reaction conditions are: reaction temperature of 440-480°C, reaction pressure of normal pressure, methanol weight space velocity of 4-8h -1The specific reaction conditions of each embodiment are shown in Table 8. The products, catalyst activity and product selectivity were analyzed using Shimadzu GC-2014 gas chromatograph, as shown in Table 8.

[0171] Table 8

[0172]

[0173] Comparative Example 1

[0174] The raw materials and preparation steps are the same as in Example 1, and the raw material ratio is adjusted. The final material ratio (molar ratio) is:

[0175] SiO2 / Al2O3=100;

[0176] NaOH / SiO2=0.18;

[0177] Trimethylethylammonium hydroxide (R) / SiO2 = 0.20;

[0178] H2O / SiO2=18.

[0179] The mixture was placed in a stainless steel reactor and heated for crystallization at 170°C and 20 rpm for 3 days. After crystallization, it was filtered, washed, and dried in an oven at 100°C overnight. The XRD spectrum of the obtained product is shown in the figure below. Fig. 9 As shown, the sample is not crystallized and has an amorphous structure, and is not SCM-36S molecular sieve.

[0180] Comparative Example 2

[0181] The raw materials and preparation steps are the same as in Example 1, and the raw material ratio is adjusted. The final material ratio (molar ratio) is:

[0182] SiO2 / Al2O3=35;

[0183] NaOH / SiO2=0.40;

[0184] Trimethylethylammonium hydroxide (R) / SiO2 = 0.20;

[0185] H2O / SiO2=18.

[0186] The mixture was placed in a stainless steel reactor and heated for crystallization at 170°C and 20 rpm for 3 days. After crystallization, it was filtered, washed, and dried in an oven at 100°C overnight. The XRD spectrum of the obtained product is shown in the figure below. Fig.10 As shown, the sample is a molecular sieve mixed with MOR structure and FER structure, not SCM-36S molecular sieve.

[0187] Comparative Example 3

[0188] The raw materials and preparation steps are the same as those in Example 1, sodium aluminate is aluminum hydroxide, and the raw material ratio is adjusted, and the final material ratio (molar ratio) is:

[0189] SiO2 / Al2O3=35;

[0190] NaOH / SiO2=0.18;

[0191] Trimethylethylammonium hydroxide (R) / SiO2 = 0.20;

[0192] H2O / SiO2=18.

[0193] The mixture was placed in a stainless steel reactor and heated for crystallization at 170°C and 20 rpm for 3 days. After crystallization, it was filtered, washed, and dried in an oven at 100°C overnight. The XRD spectrum of the obtained product was Fig. 9 Similarly, the sample is not crystallized and has an amorphous structure, and is not SCM-36S molecular sieve.

[0194] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A SCM-36S molecular sieve, It is characterized in that The molecular sieve has an X-ray diffraction pattern as shown in the following table, Wherein, a: ±0.30°, b: varies with 2θ.

2. The molecular sieve according to claim 1, in, The molecular sieve has a schematic chemical composition of "SiO 2 1 / nAl 2 O 3 1 / mR", 20≤n≤60, 0.04≤m≤0.15; preferably 25≤n≤50, 0.05≤m≤0.14; and / or The molecular sieve crystals have a flake morphology with a thickness of no more than 12 nm, a length and a width of 100-550 nm respectively; preferably, the molecular sieve crystals have a flake morphology with a thickness of no more than 10 nm, a length and a width of 120-450 nm respectively; and / or The crystals with a thickness of no more than 6 nm in the molecular sieve account for at least 60% of the total crystals.

3. The molecular sieve according to claim 1 or 2, in, The molecular sieve is a sodium type molecular sieve: Total specific surface area not less than 350 m 2 / g, preferably 350-600 m 2 / g; and / or External specific surface area not less than 180 m 2 / g, preferably 180-300 m 2 / g; and / or Total pore volume not less than 1.30 cm 3 / g, preferably 1.30-2.0 cm 3 / g; and / or The micropore volume is not less than 0.08 cm 3 / g, preferably 0.08-0.20 cm 3 / g; and / or The pore diameter of the micropores is 0.30-0.70 nanometers, preferably 0.35-0.65 nanometers.

4. The molecular sieve according to any one of claims 1 to 3, in, The molecular sieve is a hydrogen type molecular sieve: The total acid content is not less than 600 μmol / g, preferably 600-1600 μmol / g; and / or The amount of strong acid is not less than 200 μmol / g, preferably 200-600 μmol / g.

5. A method for preparing the molecular sieve according to any one of claims 1 to 4, It is characterized in that The method comprises: preparing a silicon source, sodium aluminate, sodium hydroxide, an organic structure directing agent and water into a crystallization solution, separating and drying after crystallization treatment; wherein: The Al in sodium aluminate 2 O 3 The content is 38-43% by weight, Na 2 The content of O is 30-33% by weight; The organic structure directing agent contains a trimethylethylammonium ion structure; In the crystallization solution, the silicon source is SiO 2 Sodium aluminate is measured in Al 2 O 3 The molar ratio of sodium hydroxide, organic structure directing agent calculated as trimethylethylammonium ion and water is 1: 0.016-0.050: 0.10-0.20: 0.15-0.30: 10-50.

6. The preparation method according to claim 5, in, The silicon source is selected from at least one of silica sol, silica gel and white carbon black; and / or The organic structure directing agent is a quaternary ammonium salt and / or quaternary ammonium base containing a trimethylethylammonium ion structure, preferably at least one selected from trimethylethylammonium hydroxide, trimethylethylammonium chloride, trimethylethylammonium bromide and trimethylethylammonium iodide, more preferably trimethylethylammonium hydroxide.

7. The preparation method according to claim 5 or 6, in, In the crystallization solution, the silicon source is SiO 2 Sodium aluminate is measured in Al 2 O 3 The molar ratio of sodium hydroxide, organic structure directing agent calculated as trimethylethylammonium ion and water is 1: 0.019-0.045: 0.12-0.18: 0.16-0.30: 12-45.

8. The preparation method according to any one of claims 5 to 7, in, The conditions of the crystallization treatment include: a temperature of 150-180°C, preferably 155-175°C; and / or a time of 1.5-9.0 days, and a crystallization time of 2.0-8.0 days; and / or The drying conditions include: a temperature of 40-250° C., preferably 60-50° C., and / or a drying time of 8-30 h, preferably 10-20 h.

9. The preparation method according to any one of claims 5 to 8, in, The method further comprises: performing a first calcination treatment after drying, preferably The first calcination conditions include: calcination temperature of 300-800°C, preferably 400-650°C; and / or calcination time of 1-10h, preferably 3-6h; and / or The method further comprises: performing ammonium exchange after the first calcination treatment, preferably The ammonium exchange conditions include: the ammonium salt is selected from at least one of ammonium chloride, ammonium nitrate, ammonium carbonate and ammonium sulfate; and / or the ammonium ion concentration in the ammonium salt solution is 0.1-1 mol / L; and / or the solid-liquid ratio is 1:5-1:20; and / or the temperature is 30-80°C; and / or the time is 1-8h; and / or The method further comprises: performing a second calcination after the ammonium exchange, preferably The conditions for the second calcination include: a calcination temperature of 300-800° C., preferably 400-700° C.; and / or a calcination time of 1-8 hours, preferably 2-6 hours.

10. Use of the molecular sieve according to any one of claims 1 to 4 in the preparation of an adsorbent and / or a catalyst.

11. A composition, It is characterized in that The composition comprises the molecular sieve described in any one of claims 1 to 4.

12. Use of the molecular sieve according to any one of claims 1 to 4 in alkylbenzene cracking reaction or methanol conversion to olefins and / or aromatics.

13. A methanol conversion method, It is characterized in that The method comprises: contacting methanol with a catalyst to react to obtain olefins and / or aromatics, wherein the catalyst comprises the molecular sieve according to any one of claims 1 to 4; Preferably, The contact reaction conditions include: a reaction temperature of 450-480°C; and / or a reaction pressure of 0.05-0.5 MPa, a methanol weight space velocity of 4-8 h -1 .

Citation Information

Patent Citations

  • Crystalline zeolite y

    US3130007A

  • Crystalline zeolite ZSM-5 and method of preparing the same

    US3702886A

  • Preparation of porous crystalline synthetic material comprised of silicon and titanium oxides

    US4410501A

  • Crystalline aluminosilicate PSH-3 and its process of preparation

    US4439409A

  • Composition of synthetic porous crystalline material, its synthesis and use

    US4954325A